The global decline of pollination services - Kevan, Peter G.; Viana, Blandina F. (Biodiversity (Nepean), 2003)
Pollination, the transfer of pollen from anthers to stigmas achieved mainly by animals, is vital to plant reproductive biology in almost all terrestrial ecosystems. This process is critical for the conservation and sustainability of the world's flora and fauna. The decline of pollination services caused by chemicals, pests, extreme weather, habitat destruction and/or fragmentation, reduces the reproductive output of plants. In extreme cases this could cause extinction of plants and animals and ultimately lead to changes in the landscape and in ecosystem function. Conservation concerns for pollination have started to take on a greater profile over the past decade. However, there is still a need for policies that are sensitive to the importance of pollinators. More intensive efforts are required to widen the general understanding of the essential value of plant-pollinator interactions for agricultural and natural resource conservation.